MEMETAKAN BUDAYA ORGANISASIATAS DASAR GAYA KEPEMIMPINAN DAN PENGARUHNYA TERHADAP KINERJA DOSEN - Sugeng Mulyono; Jamal Abdul Nasir (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2012)
This research aimed to describe organizational cultural and style of leadership, analyzing organizational culture pursuant to style of leadership, analyzing organizational cultural influence to performance of lecture, and analyzing the direct and indirect influence of leadership style to the Private University lecturers’ performance. In taking the sample it uses multi stages of sampling with amount of sample as much 280 lectures. Data collecting uses questioner, interview and detection of relevant document; while analysis of data uses descriptive analysis and path analysis. The results of research indicate that: style of authority leadership have a negativity effect and significant to organizational culture; style of democratic leadership and laissez faire have positive effect and significant to organizational culture; style of democratic and authoritarian leadership have a positive effect and significant to the lecturers’ performance; style of leadership laissez faire have a negative effect and significant to the lecturers’ performance; organizational cultural have a positive effect and significant to the lecturers’ performance; leadership authority and democratic style indirectly influence positively and significant to the lecturers’ performance; and leadership style of laissez faire indirectly negatively influences the lecturers’ performance.